PREVENTION OF POSTOPERATIVE WOUND COMPLICATIONS IN PATIENTS WITH VENTRAL HERNIAS AND OBESITY - Лавренко, Д.О. (World of Medicine and Biology, 2015)
In conditions of the surgical department of a multitype medical facility the results of the treatment of 166 patients with ventral hernias and obesity have been analysed. Patients were divided into 2 groups: 30 patients were treated by our proposed method (study group, the period of 2012-2015), and 136 patients who were treated by traditional medical scheme (the comparison group, the period of 2009-2012 years). To improve the results of surgical treatment of patients with ventral hernias and obesity a methodology based on comprehensive prevention of postoperative wound complications at all stages of the perioperative period have been proposed and used. According to the analysis of postoperative period it was managed to reduce the number of wound complications in patients from the main group.
Keywords: ventral hernia; obesity; wound com-plications; prevention of postoperative complications